Epidemiology of mental health status of veterans with unilateral blindness in Fars province - Z. Manaei; Kh. Abolmaali Alhossein; B. Mousavi (Afarand Scholarly Publishing Institute, 2016)
Aims: The aim of this study was to evaluate the prevalence of mental health disorders in veterans with unilateral blindness in Fars province. Methods:In a cross-sectional study in 2015, Mental Health Information of 187 veterans with unilateral blindness in Fars province was obtained using the SCL-90-R and two trained psychologists. Demographic data was including age, age at the time of injury, gender, disability percent, marital status, education, employment and having other injuries. SPSS 22 software, chi square test and Pearson correlation was used for statistical analysis. Results: The mean age at the time of study and duration of injury was 46.0 ± 4.7 and 24.9 ± 3.5 years, respectively. About half (54.0%) of them had educational level under diploma and more than half (51.3%) were unemployed or retired. In 73.8%, other injuries except unilateral blindness were observed. In total, 41.7% were suffering from mental health problems; 8.6% had one and 33.1% had two or more mental problems. Somatization (13.5%), hostility and anxiety (12.8%) were the most prevalent disorders and psychosis (8.9%) had the lowest frequency. A significant relationship between mental health problems with education (P=0.02, r=13.16) and other injuries (P=0.01, r=6.64) was observed. Conclusion: The results showed that the most common mental health problems in unilateral blind veterans in Fars province were somatization, anxiety and hostility. Planning for improving the mental health status of veterans with unilateral blindness is essential. In order to improving the mental health status of unilateral blind veterans planning, regular screening and follow up is essential.